Of gold, Spanish conquistadors, and Ibaloi generational memory - Dela Paz, Ferdinand Isidro (2013)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/3967/3613
Keywords: Books -- Reviews; Ibaloi (Philippine people); Benguet